he preparation of HEMA-MPC films for ocular drug delivery - Athmar Al-Sohani; Sahar Awwad; Peng T Shaw; Steve Brocchini (University of Huddersfield Press, 2017)
There is a need to prolong drug residence time using a biocompatible formulation in the subconjunctival space after surgery to treat glaucoma. Drug releasing discs were prepared with 2-(hydroxyethyl)methacrylate (HEMA) and 2-methacryloyl-oxyethyl phosphorylcholine (MPC). The ratio of bound water (Wb) to free water (Wf) ratio increased from 1:0.3 to 1:6.8 with increasing MPC (0 to 50%, w/w). The optimal balance between water content, SR and mechanical strength were obtained with 10% MPC (w/w) hydrogels. Water-alcohol mixtures were examined to facilitate loading of poorly soluble drugs, and they showed greater hydrogel swelling than either water or alcohol alone. The SR was 1.2 ± 0.02 and 3.3 ± 0.1 for water and water:ethanol (1:1) respectively. HEMA-MPC (10%) discs were loaded with dexamethasone using either water:ethanol (1:1) or methanol alone. Drug release was examined in an outflow rig model that mimics the subconjunctival space in the eye. Dexamethasone loading increased from 0.3 to 1.9 mg/disc when the solvent was changed from water:ethanol (1:1) to methanol with the dexamethasone half-life (t½) increasing from 1.9 to 9.7 days respectively. These encouraging results indicate that HEMA-MPC hydrogels have the potential to sustain the residence time of a drug in the subconjunctival space of the eye.